PENGARUH HARGA DAN CITRA DESTINASI TERHADAP NIAT BERKUNJUNG KEMBALI MELALUI KEPUASAN (Studi pada Wisatawan Domestik Kebun Raya Bogor) - Verissa Rana Khansa; Naili Farida (Universitas Diponegoro, 2016)
Travelling has become a part of some Indonesian’s needs nowadays. Enterprises of tourism industry compete to increase the number of visit by reaching out the tourist’s satisfaction which associated with revisit intention. It’s what Bogor Botanical Garden does too, but there is a fluctuate decline of visitor number in 2011 until 2015. The aim of this study is determining the effect of price and destination image towards revisit intention through satisfaction in Bogor Botanical Garden. The type of this research is explanatory research with questionnaires and interview. The amounts of sample are 100 domestic tourists whom age is at least 17 years old. This study uses qualitative and quantitative analysis technique. Quantitative analysis is using validity test, reliability test, the coefficient of correlation, the coefficient of determination, simple and multiple regression analysis, t test one tail, two stages regression and sobel test uses Preacher’s Tool. The result shows that there is a positive effect of price and destination image partially towards satisfaction and satisfaction has positive effect towards revisit intention. The result of two stages regression shows that price has bigger effect than destination image towards satisfaction, and satisfaction affects revisit intention. Then, satisfaction has a role as mediation that indicates an indirect effect of price and destination image towards revisit intention. The suggestions for Bogor Botanical Garden are determining competitive price which appropriate to facility, making kind of festival or event, putting employees inside Bogor Botanical Garden and redecorating the museum.